THE RISE OF RELIGIOUS CONSERVATISM IN THE U.S. SINCE THE PRESIDENCY OF DONALD TRUMP - Jenny; Manlee, Chrystle Feodore (GENEVA: JURNAL TEOLOGI DAN MISI, 2024)
It has long been understood that there is something peculiar, even paradoxical, about conservatism in America. For most Europeans who came to America, the whole purpose of their difficult and disruptive journey to the New World was not to conserve European institutions but to leave them behind and to create something new, often an entirely new life, and even a new identity, for themselves. Conservatives have been divided into: (1) those who are most concerned about economic or fiscal issues, that is, pro-business or “free-enterprise” conservatives; (2) those most concerned with religious or social issues, that is, pro-church or “traditional-values” conservatives; and (3) those most concerned with national-security or defense issues, that is, pro-military or “patriotic” conservatives. For a while, especially during the 1980s, it may have seemed that these three kinds of conservatives were natural allies, that they had an “elective affinity” for each other, and that there was no significant contradiction between them. In a pattern similar to that of economic conservatism, in Europe an established state church shaped religious and moral conditions. In America, particularly after the adoption of the U.S. Constitution, religious and moral conditions were instead shaped by the separation of church and state and even by religious pluralism. Following the 2016 presidential election of Donald Trump, many scholars have recognised the crucial role of Christian evangelical support for his triumphed victor. Here, we realize there is an interesting relation between faith and politics in the American voting system. the underlying arguments that we wish to portray in this article is: 1) that Trump facilitated more religious conservatives through a socially constructed approach, and 2) that this approach of conservatism has further led to the decline of U.S. social and political legitimacy due to the massive social issues that happened.